Sources, distributions, and burial efficiency of terrigenous organic matter in surface sediments from the Yellow River mouth, northeast China. (April 2018) - Sun, Dayang; Tang, Jianhui; He, Yuxin; Liao, Weisen; Sun, Yongge
Highlights: Behaviors and fates of soil OC and fossil OC in the Yellow River mouth were studied. Terrigenous OC accumulation is controlled by hydrodynamic processes. The relative contribution of terrigenous OC ranges from 14% to 57% in Laizhou Bay. On average, 58% fossil OC exported by the Yellow River is lost during deposition. Abstract: Organic geochemical studies of surface sediments from Laizhou Bay, the Yellow River mouth, northeast China, were conducted to reveal the sources, distributions, and burial efficiency of terrigenous OC exported by the Yellow River. Bulk OC contents and δ 13 Corg values from 204 samples show that terrigenous OC mainly accumulates in two muddy patches, basically controlled by hydrodynamic conditions. Distributions and stable carbon isotopic compositions of individual n -alkanes from 45 samples suggest that short-chain n -alkanes, with even carbon-number predominance, are most likely microbial products from degradation of riverine fossil OC, whereas long-chain odd-numbered n -alkanes ( n -C27, n -C29 and n -C31 ) and long-chain even-numbered n -alkanes ( n -C26, n -C28 and n -C30 ) are representative of riverine soil OC and fossil OC, respectively. Integrated with previous reports of ∼100% burial efficiency of soil OC in the Yellow River mouth, concentration ratios of n -C27+29+31 to OC and n -C26+28+30 to n -C27+29+31 from the riverine particles to surface sediments in Laizhou Bay were constructed to indicate relative terrigenous OC contributions and fossil OC burial efficiency, respectively. The results suggest that the terrigenous OC contribution ranges from 14% to 57% in Laizhou Bay, with the highest values in the two muddy patches as well as in areas near the river mouth. The fossil OC burial efficiency ranges from 36% to 76%, with an TOC-weighted mean value of 42%. The 58% fossil OC lost during the transport and burial processes in the Yellow River mouth may provide a significant CO2 source.